Modeling prehensile actions for the evaluation of tangible user interfaces. - Christou, Georgios.; Ritter, Frank E.; Jacob, Robert J. K. (Tufts University. Tisch Library., 2017)
Prehension, or reaching-to-grasp is a very common movement performed by users of Tangible User Interfaces (TUIs) because through this movement users can manipulate tangible artifacts. Here we present an experiment that provides evidence towards the hypothesis that prehensile movements can be modeled based on the amplitude of the prehension movement. We then explore consequences of this evidence on the modeling and evaluation of TUIs using tools that can predict task completion times, such as Goals, Operators, Methods and Selection Rules (GOMS), as well as the implications for TUIs compared to Direct Manipulation Interfaces. © 2008 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works.